The Effectiveness of Audiobook in Teaching Question Tags: Experiences Learned from Expanding Countries - Edi Sunjayanto Masykuri; Svetlana V. Androsova; Semi Sukarni; Au Thien Wan; Ilahe Mamadova (Journal of Languages and Language Teaching, 2023)
The choice of instructional media is pivotal, requiring innovation and practicality. One such medium that has demonstrated considerable promise is the Audiobook, whose effectiveness has already been demonstrated in the context of ELT in Azerbaijan. Building upon this precedent, the present study seeks to adapt this medium for implementation in Indonesia, employing distinct instruments and datasets. The overarching aim of this research endeavor is to assess the viability of Audiobooks as an instructional medium for teaching question tags to ninth-grade students in Indonesia. To rigorously investigate this question, the research design adopts a quantitative approach, utilizing an experimental methodology. The study selects two classes from the ninth-grade population as the sample, encompassing a total of 56 students. Data analysis techniques encompass both descriptive and inferential methods, with the Mann-Whitney U-test applied.. The findings reveal a noteworthy outcome: the achievement of students in the experimental group, exposed to Audiobook-based instruction, surpasses that of the control group. Crucially, this difference is statistically significant, as evidenced by the z-value exceeding the critical z-table value (6.198 > 1.96). Consequently, it is possible to conclude that Audiobooks serve as an effective method for teaching question tags to ninth-grade students in Indonesian junior high schools. These results contribute to the growing body of evidence supporting the integration of innovative media, such as Audiobooks, into ELT practices. Moreover, they underscore the adaptability and potential transferability of such instructional approaches across diverse educational contexts, emphasizing the importance of pedagogical innovation in fostering effective language learning.